Physical Condition Profile Of Athletes Of SSB Kancil Mas Academy Class U-15 - Anggia Ningsih; Deden Akbar Izzuddin; Muhammad Arief Setiawan; Qorry Armen Gemael; Habibi Hadi Wijaya (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study focuses on the physical condition profile of athletes at the Kancil Mas Football School (SSB) U-15 category, to evaluate the level of physical fitness of athletes in supporting their optimal performance on the field. The physical conditions measured include endurance, speed, agility, and leg muscle explosive power, which are key elements in the game of football. This study uses a quantitative descriptive method, with instruments in the form of physical tests such as the Bleep Test, 30-meter run, shuttle run, and standing long jump. The results showed that most athletes had adequate physical condition, with the majority of athletes in the "Good" category for speed and explosive power, and the "Fair" category for endurance and agility. However, aerobic endurance and agility still require more attention to achieve a higher level of performance. This study provides important insights for coaches and training program managers at SSB Kancil Mas to design more targeted development strategies. These findings also emphasize the importance of continuous evaluation to ensure athlete readiness in facing competition. Through a data-based approach, this research is expected to be the basis for effective decision-making in improving the quality of coaching for young athletes at SSB Kancil Mas.